Work Stress, Work Environment, And Teacher Performance In Islamic High Schools - Kholis, Nur; Rohma, Hardina; Maesaroh, Imas (International Journal of Scientific Research and Management (IJSRM), 2024)
This study investigates the effects of demographic factors, workplace stress, and the work environment on teachers' performance. Employing quantitative methodologies, it analyzes responses from teachers (Men = 51.7%, Women = 48.3%) at three Islamic Higher Schools or Madrasah Aliyah in Indonesia. Data was gathered through questionnaires directly handed out to respondents. The questionnaires included some demographic details of the participants, such as their gender, age, level of education, duration of employment, and monthly income. A Likert scale was employed to record respondents’ opinions on work stress, work environment, and teacher performance. Data was tested for normality, heteroskedasticity, and multicollinearity before finally being analyzed using multiple linear regression. Findings indicate a marginal performance advantage for married teachers over their single counterparts (B = .234, p = .063), meaning that married teachers perform slightly better than nonmarried teachers. Workplace stress was found to have a negligible effect on teacher performance (B = .160, p = .187), suggesting that teachers' performance did not depend on their being stressed or unstressed. Furthermore, the work environment significantly influences teacher performance (B = .345, p = .006), meaning a conducive work environment leads to better teacher performance. These results highlight the importance of creating a supportive and conducive workplace to enhance teacher productivity, suggesting that educational institutions should prioritize improvements in the work environment to foster optimal teacher performance.